Rock the Boat! Shaken by the COVID-19 Crisis: A Review on Teachers’ Competencies in ICT - Montiel, Hugo; Gomez-Zermeño, Marcela Georgina (Frontiers in Education, 2022)
The COVID-19 pandemic suddenly brought great challenges to the continuation of education. Institutions had to elect between abruptly finishingpre-maturely ending their current school cycles or shifting to an online, flexible environment that had to deal with the digital divide in internet access. As part of its Sustainable Development Agenda, UNESCO developed in 2018 the "Information and Communications Technology Competency Framework for Teachers" in 2018 to help institutions achieve digital literacy and reduce the digital divide. A systematic literature review (SLR) was conducted, identifying 23 studies on the use of ICT tools during COVID-19 educational disruptions in the database ProQuest Central and Google Scholar from August 2019 to August 2020. The results of this SLR showed that frameworks such as that of UNESCO could guide institutions to fast-track the development of educational strategies for post-crisis, COVID-19 implementation. Also, findings suggest an increase in the use of ICTs in learning environments, which will encourage organizations like UNESCO to develop plans and projects, such as the ICT framework further. Coping with the challenges of today's learning environments is urgent; it is already time to "Rock the boat!" Introduction